Correction to: Lifestyle factors and lung cancer risk among never smokers in the Canadian Partnership for Tomorrow’s Health (CanPath) - Rachel A. Murphy; Maryam Darvishian; Jia Qi; Yixian Chen; Quincy Chu; Jennifer Vena; Trevor J. B. Dummer; Nhu Le; Ellen Sweeney; Vanessa DeClercq; Scott A. Grandy; Melanie R. Keats; et al. (Cancer Causes & Control, 2022)

Lifestyle factors and lung cancer risk among never smokers in the Canadian Partnership for Tomorrow’s Health (CanPath) - Rachel A. Murphy; Maryam Darvishian; Jia Qi; Yixian Chen; Quincy Chu; Jennifer Vena; Trevor J. B. Dummer; Nhu Le; Ellen Sweeney; Vanessa DeClercq; Scott A. Grandy; Melanie R. Keats; et al. (Cancer Causes & Control, 2022)

The relationship between anthropometric measures and cardiometabolic health in shift work: findings from the Atlantic PATH Cohort Study - Ellen Sweeney; Zhijie Michael Yu; Trevor J. B. Dummer; Yunsong Cui; Vanessa DeClercq; Cynthia Forbes; Scott A. Grandy; Melanie Keats; Louise Parker; Anil Adisesh (International Archives of Occupational and Environmental Health, 2020)

Sickeningly Sweet: L‐rhamnose stimulates Flavobacterium columnare biofilm formation and virulence - M D Lange; B D Farmer; A M Declercq; E Peatman; A Decostere; B H Beck (Journal of Fish Diseases, 2017)
Flavobacterium columnare , the causative agent of columnaris disease, causes substantial mortality worldwide in numerous freshwater finfish species. Due to its global significance and impact on the aquaculture industry continual efforts to better understand basic mechanisms that contribute to disease are urgently needed. The current work sought to evaluate the effect of L‐rhamnose on the growth characteristics of F. columnare . While we initially did not observe any key changes during the total growth of F. columnare isolates tested when treated with L‐rhamnose, it soon became apparent that the difference lies in the ability of this carbohydrate to facilitate the formation of biofilms. The addition of different concentrations of L‐rhamnose consistently promoted the development of biofilms among different F. columnare isolates; however, it does not appear to be sufficient as a sole carbon source for biofilm growth. Our data also suggest that iron acquisition machinery is required for biofilm development. Finally, the addition of different concentrations of L‐rhamnose to F. columnare prior to a laboratory challenge increased mortality rates in channel catfish ( Ictalurus punctatus ) as compared to controls. These results provide further evidence that biofilm formation is an integral virulence factor in the initiation of disease in fish.

Isolation and characterization of Pseudomonas syringae pv. porri from leek in Flanders - S. Rombouts; J. Van Vaerenbergh; A. Volckaert; S. Baeyen; T. De Langhe; B. Declercq; R. Lavigne; M. Maes (European Journal of Plant Pathology, 2016)

β-Alanine does not act through branched-chain amino acid catabolism in carp, a species with low muscular carnosine storage - F. Geda; A. Declercq; A. Decostere; A. Lauwaerts; B. Wuyts; W. Derave; G. P. J. Janssens (Fish Physiology and Biochemistry, 2015)

Molecular characterization of Phytophthora porri and closely related species and their pathogenicity on leek (Allium porrum) - B. Declercq; E. Van Buyten; S. Claeys; N. Cap; J. De Nies; S. Pollet; M. Höfte (European Journal of Plant Pathology, 2010)